IMPLEMENTASI PLAN DO CHECK ACTION PADA PRODUK CRUDE PALM OIL - Ainul Haq; Syarifuddin Nasution; Matri Yanti Hasugian (Asosiasi Dosen Muda Indonesia, 2024)
PDCA (Plan-do- check-action)is a management concept used to achieve continuous improvement in an organization. The problem that occurs in quality control is how to reduce the level of product defectscrude palm oil.The aim of this research is to identify types of defects that often occur, identify factors that cause defects in products and implement product quality improvementscrude palm oil(CPO) at PT. BPSJ with approach Plan-Do-Check-Action(PDCA). In the Pareto diagram, there are three types of biggest defects in crude palm oil products, namely the high ALB content defect type with a percentage of 39%, while for water content the percentage is 33% and for impurity content it is 29%. Factors causing defects in crude palm oil products(crude palm oil) based on fishbonecaused by several factors. Defects at high ALB levels are caused by five main factors, one of which is the human factor, namely the lack of accuracy during operations from operators/employees. Defects at high water content are caused by the main factor that the raw materials obtained do not comply with fruit acceptance standards. Defects at high levels of dirt are caused by one factor, namely the work environment, where cleanliness is not maintained in the sorting and production areas. Based on the results of implementing improvements made in an effort to increase the quality of crude palm oil products(crude palm oil)namely reducing the number of defects in crude palm oil products. The number of defects obtained before repairs were carried out for ALB levels was 52 samples to 42 samples, water content was 44 samples to 27 samples and dirt content was 39 samples to 25 samples.